On Development of Parallel Algorithms for Solving Parabolic and Elliptic Equations - Zhukov, V. T.; Feodoritova, O. B. (Journal of mathematical sciences (New York, N.Y.), 2021)
In this paper, we present results of the development of certain parallel numerical methods for solving three-dimensional evolutionary and stationary problems of diffusion and heat transfer. We present a detailed description of a special, explicit iteration scheme for parabolic equations and discuss a multigrid technology used for solving elliptic equations and implicit schemes for parabolic equations.